Comparison of teacher and student perceptions of formative assessment feedback practices and association with individual student characteristics - van der Kleij, Fabienne M. (Teaching and teacher education, 2019)
This study (1) investigated similarities and differences in feedback perceptions among teachers and students and (2) explored the association between individual student characteristics and students' feedback perceptions. Survey data were collected from 59 teachers and 186 students in secondary English and mathematics classes in five Australian schools. Feedback quality was perceived more positively by teachers than students, and English teachers reported higher levels of facilitation of feedback use than students. Student self-reported levels of self-efficacy, intrinsic values and self-regulation predicted students’ perceptions of feedback quality. These individual student characteristics mediated the relationship between student achievement levels and feedback quality perceptions. •Investigated teacher and student feedback perceptions in secondary English and mathematics using surveys.•Overall, feedback quality was perceived more positively by teachers than students.•Teachers were significantly more positive about facilitation of feedback use than students in English.•Students' self-reported self-efficacy, intrinsic values and self-regulation predicted their perceptions of feedback quality.•Self-efficacy, intrinsic values + self-regulation mediated the impact of achievement level on feedback quality perceptions.